Transformation of civilizational values of Ukrainians in terms of the regionalization of the world economy - Grygorii Shamborovskyi (Cхід)
Although there has been a lot of research done on the civilizational belonging and identity of Ukrainians, issues of uncertainty of the Ukrainian nation regarding its own moral and socioeconomic values in the current terms of overcoming the communist legacy and the accumulation of primitive capital have remain unexplored. Ukrainian scholarly publications also lack research on geopolitical processes and their impact on the Ukrainian consciousness. The article is on the research of the civilizational identity, consciousness, and the role of Ukrainians as a distinctive people that is shaped by two opposite systems of moral and socioeconomic values of Europe andAsia. On the basis of civilizational theories and current research on socioeconomic values in Ukraine, the author analyzes internal and external factors of the transformation and priority of values of Ukrainians in the beginning of the twenty-first century and considers the current state of consolidation and welfare of the population of Ukraine in the conditions of the regionalization of the world economy. The author gives reasons for the decline of economic culture and destruction of social relations in Ukrainian society due to the lack of general positions of the national political and economic elite regarding the objectives, goals, and purpose ofUkraineon the border of two civilizations. The article covers the problems of geopolitical identity and the formation of a new civilized worldview of Ukrainians, based on the global economic culture.